Situações migratórias do ensino superior no Brasil: a inserção, o acesso e a permanência dos estudantes da diáspora africana - Yeboah, Jacob (2021)
The aim of this research was to investigate the diverse immigration situations experienced by diaspora African tertiary students in Brazil. Data was collected through a method known as “reflexive interview”, using a qualitative research approach. This research procedure is based on the subjective inter-personal relationship between the interviewer and the participant. Through this method, the students answered the following questions: what are the reasons for which they decided to leave their country of origin in pursuit of higher education in Brazil? What are some of the difficulties or challenges they faced during their arrival and insertion into the Brazilian society as well as the university environment? And what is their plans for the future after returning to their home country? The research participants where four immigrants from sub-Saharan African countries: Kenya, Ivory Coast, Benin and Cape Verde, studying in two Universities in Brazil. Three of them came through a scholarship scheme called PECG, studying in the University of São Paulo while one came through the help of his family, studying in the Pontifical Catholic University of São Paulo. The information obtained from the interview was analyzed first through a careful reading of the written text in other to form significant units and categories of the content analyses. The research revealed that the emigration of most of the students were linked to poor conditions of life in their home countries: personal desire, unfavorable financial situation, limited University programs offered in their countries, availability of scholarships in Brazil, LGBTQ+ issue, family investments, cultural and language proximity, the quality of education and the value attached to foreign degrees, lack of employment and religious influence. On the other hand, while in Brazil, these students face many challenges like difficulties in adapting to the culture, worries about their new adventures, lack of social integration, financial difficulties, racial discrimination, prejudices, and xenophobia. And finally, about their future, some of them expressed a desire to return in other to rebuild their countries while others do not want to go back immediately after completing their studies due to the poor economic conditions found in their countries of origin